Situs Inversus Totalis: A Clinical Review - Eitler K; Bibok A; Telkes G (International Journal of General Medicine, 2022)
Katalin Eitler,1 András Bibok,2 Gábor Telkes1 1Department of Surgery, Transplantation and Gastroenterology, Semmelweis University, Budapest, Hungary; 2Medical Imaging Centre, Semmelweis University, Budapest, HungaryCorrespondence: Gábor Telkes, Department of Surgery, Transplantation and Gastroenterology, Semmelweis University, VIII. Baross u.23., Budapest, H-1082, Hungary, Tel +36 20 825 8593, Email telkesdr@gmail.comAbstract: Situs inversus totalis is a rare congenital abnormality characterized by a mirror-image transposition of both the abdominal and the thoracic organs. While this anomaly is known since the ancient times, practicing doctors do not have much experience with it. Laterality is established early in development, and any failure in that process might lead to a wide variety of disorders which may be partial or complete. Situs solitus describes the normal anatomy, situs inversus is the complete reversal, and situs ambiguous is used for any other abnormality of left-right development. Sidedness is regulated by genes: over 100 genes have been linked to laterality defects. Frequency of situs inversus is 1:10,000 and is more frequent in males: 1.5:1. Advanced imaging modalities can be used to assess fine anatomical details, which play a crucial role in these cases to plan radiologic or surgical interventions. Percutaneous biliary procedures, portal vein embolization are really challenging procedures in SIT patients due to the mirror effect. As most surgeons are right-handed, SIT operations can cause difficulties: handling the instruments with their left hand or the pedals with their left foot can be uncomfortable Organ, especially liver transplantation represents an extraordinary surgical challenge. Solutions to overcome the anatomic differences include the use of segment or reduced size graft with rotation, modified piggy-back technique, side to-side caval anastomosis, and vascular conduit. Because of its rarity and special nature, surgical patients with situs inversus may require more flexibility and creativity from the surgical team.Keywords: situs inversus totalis, left-right asymmetry, mirror-image transposition, kidney transplantation, liver transplantation, organ donation